1987
DOI: 10.1073/pnas.84.19.6760
|View full text |Cite
|
Sign up to set email alerts
|

Localization of atrial natriuretic peptide mRNA and immunoreactivity in the rat heart and human atrial appendage.

Abstract: The localization of mRNA encoding preproatrial natriuretic peptide was investigated in tissue sections and cultures of rat heart and in sections of human right atrial appendage using the technique of in situ hybridization with 32P-and 35S-labeled RNA probes. Rat atrial natriuretic peptide (ANP) transcripts were demonstrated in numerous atrial myocytes and, to a lesser extent, in ventricular myocytes in both tissue sections and newborn rat heart cultures. These rmdings are consistent with those obtained by RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 34 publications
0
64
0
Order By: Relevance
“…In situ hybridization was performed as previously described (Hamid et al, 1987;Tsicopoulos et al, 1998). Briefly, sections were hybridized with 35 S-labeled riboprobes (2 ϫ 10 6 cpm per section) in hybridization buffer containing 50 mM dithiothreitol (Promega, Madison, Wisconsin).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…In situ hybridization was performed as previously described (Hamid et al, 1987;Tsicopoulos et al, 1998). Briefly, sections were hybridized with 35 S-labeled riboprobes (2 ϫ 10 6 cpm per section) in hybridization buffer containing 50 mM dithiothreitol (Promega, Madison, Wisconsin).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…Atrial natriuretic factor is expressed at very high levels in fetal atrium and ventricle (Block et al, 1986;Kikuchi et al, 1987), and is restricted to myocardial cells in the heart (Hamid et al, 1987). Induction of ANF expression was identified in this study as a marker for the differentiation of cardiac myoblasts in culture.…”
Section: Discussionmentioning
confidence: 79%
“…Expression of ANF has been observed at high levels in fetal atrium and ventricle (Bloch et al, 1986), and in situ hybridization experiments (Hamid et al, 1987) have revealed ANF transcripts in atrial and ventricular myocytes and not in other types of cells in the heart. Expression of ANF therefore represents a useful marker of cardiac myogenesis.…”
Section: Differentiation Of Human Cardiac Myoblasts Results In the Inmentioning
confidence: 99%
“…It has been reported that the most intensely staining granules are localized in the atrial appendages [13,14]. There is still a need for better mapping of the ANP producing areas, [8] and it is claimed that 30 % of the ANP in the heart is contained in the LAA [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore resting levels of natriuretic peptides are higher in chronic heart failure and atrial fibrillation compared with normal [1,11,12]. ANP gene transcripts have been shown in both atrial and ventricular myocytes; however, the level of ventricular ANP transcription is generally lower than that found in the atria [1,9,13].…”
Section: Introductionmentioning
confidence: 99%